Understanding Chinese Bond Yields and their Role in Monetary Policy - Porter, Nathan; Cassola, Nuno. (Washington, D.C. : International Monetary Fund, 2011)
China's financial prices are informative enough for the PBC to introduce a monetary policy framework centered around interest rates. While bond yields are not fully efficient?reflecting regulation, liquidity, and segmentation?we find they contain considerable information about the state of the economy as well as evidence of an emerging transmission channel: changes in PBC rates influence the structure of Treasury, financial, and corporate bond yield curves, which are then associated with changes in growth and inflation. Coporate spreads are also a leading indicator of growth and inflation. While further liberalization will strengthen both efficiency and transmission, several necessary elements to move towards indirect monetary policy are already in place.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet